Drosophila Reporter Vectors Compatible with ΦC31 Integrase Transgenesis Techniques and Their Use to Generate New Notch Reporter Fly Lines - Housden, Ben E. (Genetics Society of America, 2012)
Complex spatial and temporal regulation of gene activity is fundamental to development and homeostasis. The ability to decipher the DNA sequences that accurately coordinate gene expression is, therefore, of primary importance. One way to assess the functions of DNA elements entails their fusion to fluorescent reporter genes. This powerful approach makes it possible to visualize their regulatory capabilities when reintroduced into the developing animal. Transgenic studies in Drosophila have recently advanced with the introduction of site-specific, ΦC31 integrase–mediated approaches. However, most existing Drosophila reporter vectors are not compatible with this new approach and have become obsolete. Here we describe a new series of fluorescent reporter vectors optimized for use with ΦC31 transgenesis. By using these vectors to generate a set of Notch reporter fly lines, we demonstrate their efficacy in reporting the function of gene regulatory elements.